(3MGOj GdCQhGM Edi HdGO GdCaQGMs - (3eMeO Hf CHj HcQ Hf CjhH Hf bje GdLhRjg, GHf Gdbje, TeS GdOjf, CHh YHO Gddg, J (B751 (3g` s ((3eMeO Hf YjSi Hf YHOGddg Hf SdjeGf GdHYdj GdMfHdj s)
(3ChdgG (B:s
(3CeG HYO aEf Gddg SHMGfg de jNdb YHKoG hde jJQcge SOi Hd Ndbge dCeQ YXje hNWH LSje s
(3BNQgG (B:s
(3hdjS aj GdBjI eG jOd Ydi Pdc Hd JOd Ydi Cf Chd OYGFge GdJSHjM hBNQg GdMeO BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B56s
Keywords: (3GdJUha hGdBOGH GdTQYjIs